Effect of different positions of hollow section on the high strength concrete beam - Rokiah, Othman; Mohd Arif, Sulaiman; Chong, B. W.; Wong, C. W.; Youventharan, Duraisamy; Putra Jaya, Ramadhansyah; Nadiatul Adilah, Ahmad Abdul Ghani (IOP Science, 2021)
Today, the construction industry is continuously looking for lighter and high strength concrete (HSC) beams especially for high rise building. This research reported the effect of different positions of hollow section on the HSC beam containing eggshell powder (ESP) as partial cement replacement and tire crumb (TC) as partial sand replacement. Sustainable and high strength concrete is now widely used as a structural component like beam, slab and wall due to environmental impact. The hollow section also can reduce the dead loads which contribute to seismic effect in high rise buildings. Furthermore, eggshell is an agricultural waste that is generally considered worthless and is mostly disposed of because it leads to pollution, but it has similar properties as lime that used to be raw material to produce cement. In this study, 10% TC is used as partial sand replacement to produce a green concrete to make it more sustainable in construction. The experimental program consists of casting and testing high strength concrete beams of size 150 x 200 x 1500 mm with different positions of circular hollow sections. To study the flexural behaviour, all beams are tested after 28 days of curing subjected to four-points bending test in order to analyse the effect of different position of hollow section on the strength, deflection and mode of failure of HSC beam. Based on the experimental result, solid beam (SB) exhibits the higher strength with maximum loading of 156.45kN and flexural strength up to 39.11N/mm2. Besides, one hollow beam (OHB) and two vertical hollow beams (TVHB) show a better result in deflection compared to solid beam (SB). However, the two horizontal hollow beam (THHB) exhibits better performance in strength, with nearly 6.5% less than the SB. Conclusively, the position of the hollow beam affects the strength and deflection of the beam. All the beams experienced shear crack and flexural crack. The two horizontal hollow beams (THHB) can be used as a light structure beam of a building especially for the roof beam which receives less loading from the roof.